Human milk-derived 5′-UMP promotes thermogenesis and mitochondrial biogenesis to ameliorate obesity - Zhang, Ling; Peng, Zhou; Lin, Caiyu; Hu, Haixia; Du, Juan; Huang, Siqi; Huang, Shan; Gao, Jianfang; Guo, Xirong (Frontiers in Nutrition, 2025)
BackgroundTraditional obesity interventions are often unsuitable for children. Breastfeeding has been shown to reduce obesity risk, potentially through bioactive metabolites in human milk. Here, we identified a human milk-derived metabolite, uridine 5′-monophosphate (5′-UMP), whose role in lipid metabolism and thermogenesis remains largely unknown.MethodsUntargeted metabolomics was performed on colostrum samples from obese and healthy mothers to identify obesity-associated metabolites. Zebrafish larvae and human preadipocytes were used to evaluate the anti-obesity effects of 5′-UMP. Lipid accumulation was assessed by Oil Red O and Nile Red staining, while mitochondrial function was analyzed using transgenic zebrafish [Tg(Xla. Eef1a1: mlsEGFP)] and fluorescent imaging.ResultsPyrimidine metabolism was significantly enriched in obese mothers, with orotate and 5′-UMP levels altered. Targeted analysis confirmed the presence of 5′-UMP in colostrum. Zebrafish toxicity assays confirmed 5′-UMP safety up to 200 μM. In the high-fat diet-induced zebrafish obesity model, 5′-UMP treatment significantly reduced abdominal lipid accumulation. In adipocytes, 5′-UMP enhanced mitochondrial respiration and increased mRNA and protein expression of PGC1-α and UCP1. Furthermore, mitochondrial fluorescence intensity and protein levels of NRF1 and MFN2 were elevated, indicating enhanced mitochondrial biogenesis and activity.ConclusionMaternal obesity is associated with changes in the human milk metabolome. 5′-UMP, a nucleotide metabolite enriched in human milk, promotes thermogenesis and mitochondrial activation, effectively ameliorating obesity in zebrafish and human adipocytes. These findings support its potential as a safe, milk-derived therapeutic candidate for pediatric obesity intervention.